Hypertensive Urgency in Tanzanian Adults: A 1-Year Prospective Study. (10th August 2020) - Reis, Karl G; Wilson, Raymond; Kalokola, Fredrick; Wajanga, Bahati; Lee, Myung-Hee; Safford, Monika; Peck, Robert N
Abstract: BACKGROUND: Hypertensive urgency is associated with a high risk for cardiovascular events and mortality in the United States and Europe, but data from low-income countries and interventions to improve outcomes are lacking. METHODS: We conducted a 1-year prospective study of the prevalence and outcomes of hypertensive urgency (blood pressure (BP) ≥180 mm Hg/120 mm Hg without end-organ damage) in a busy outpatient clinic in Tanzania. RESULTS: Of 7, 600 consecutive adult outpatients screened with 3 unattended automated BP measurements according to standard protocol, the prevalence of hypertensive crisis was 199/7, 600 (2.6%) (BP ≥180 mm Hg/120 mm Hg) and the prevalence of hypertensive urgency was 164/7, 600 (2.2%). Among 150 enrolled patients with hypertensive urgency, median age was 62 years (54–68), 101 (67.3%) were women, and 53 (35%) were either hospitalized or died within 1 year. In a multivariate model, the strongest predictor of hospitalization/death was self-reported medication adherence on a 3 question scale (hazard ratio: 0.06, P < 0.001); 90% of participants with poor adherence were hospitalized or died within 1 year. CONCLUSIONS: Patients with hypertensive urgency in Africa are at high risk of poor outcomes. Clinicians can identify the patients at highest risk for poor outcomes with simple questions related treatment adherence. New interventions are needed to improve medication adherence in patients with hypertensive urgency.